PENDEKATAN PROCESS WRITING DALAM PEMBELAJARAN MENULIS TEKS ARGUMENTASI PADA SISWA SMA: KAJIAN LITERATUR SISTEMATIS - Misa Febriana; Siti Enik Mukhoiyaroh Bambang (Universitas Nias Raya, 2026)
This study is a Systematic Literature Review (SLR) aimed at examining the effectiveness of the process writing approach in teaching argumentative text writing among senior high school students. Using the PRISMA 2020 protocol, this review analyzed 25 nationally and internationally reputable journal articles published between 2021 and 2026. The findings reveal that 22 out of 25 articles (88%) reported significant improvements in students' argumentative writing quality through the process writing approach, with effect sizes ranging from d = 0.70–0.85 (large effect category). Specifically, students' mean scores increased from 65.4 to 78.9, with a margin of 12.3 points higher than the control group. The integration of process writing with structured peer feedback, digital technology, and genre-based approaches proved to yield more substantial improvements. However, this review also uncovered a cognitive-affective paradox: improvements in writing quality were not automatically accompanied by a reduction in students' writing apprehension. Key implementation challenges include curriculum time constraints, low initial motivation, superficial revision tendencies, and limited teacher competence in facilitating meaningful formative feedback.